Alkali additives enable efficient large area (>55 cm²) slot-die coated perovskite solar modules - Rana, Prem Jyoti Singh (2022)
Typical fabrication methods for laboratory-scale (<1 cm2) perovskite solar cells (PSCs) are undeniably not scalable and the control of crystallization of large-area perovskite layer for commercial sized modules is also particularly challenging. Here, a seed-assisted crystallization approach is demonstrated through addition of alkali salts, CsPbBr3 and KPb2Br5, to the perovskite precursor ink for enabling homogeneous and highly crystalline large-area Cs0.15FA0.85Pb(I0.83Br0.17)3 (CsFA) perovskite films via scalable slot-die coating technique. X-ray photoelectron spectroscopy analysis reveals the segregation of potassium ions at SnO2/perovskite interface which serve as nucleation sites for the crystallization of perovskite layer. The uniformly slot-die coated CsFA films (100 cm2) from the additives containing precursor inks possess larger grains with enhanced optoelectronic properties and the corresponding devices display higher reproducibility and consistency. A champion device efficiency of 18.94% under 1 sun illumination for slot-die coated PSCs in n-type/intrinsic/p-type structure is demonstrated with improved stability with 82% of its initial efficiency tested at 65 °C for 1150 h. The slot-die coated methylammonium-free perovskite module with an active area of 57.5 cm2 shows an efficiency of 16.22% and retains 82% of its initial efficiency after 4800 h under 30% relative humidity without encapsulation.